1Progress, applications, challenges and prospects of protein purification technology - Du, Miao; Hou, Zhuru; Liu, Ling; Xuan, Yan; Chen, Xiaocong; Fan, Lei; Li, Zhuoxi; Xu, Benjin (Frontiers in Bioengineering and Biotechnology, 2022)
Protein is one of the most important biological macromolecules in life, which plays a vital role in cell growth, development, movement, heredity, reproduction and other life activities. High quality isolation and purification is an essential step in the study of the structure and function of target proteins. Therefore, the development of protein purification technologies has great theoretical and practical significance in exploring the laws of life activities and guiding production practice. Up to now, there is no forthcoming method to extract any proteins from a complex system, and the field of protein purification still faces significant opportunities and challenges. Conventional protein purification generally include three steps: pretreatment, rough fractionation, and fine fractionation. Each of the step will significantly affect the purity, yield and the activity of the target protein. The present review focuses on the principle and process of protein purification, recent advances, and the application of this technology in the life and health industry as well as its far-reaching impact, so as to promote the research of protein structure and function, drug development and precision medicine, and bring new insights to researchers in related fields.